THE UNITED NATIONS TRUSTEESHIP COUNCIL AND THE TRUSTEESHIP SYSTEM: JUSTIFICATIONS FOR REVIVAL AND LEGAL OBSTACLES - Ahmad Risyad Sumartapraja (International Law Department, Faculty of Law Universitas Padjadjaran, 2021)
The Trusteeship Council as a principle organ of the United Nations has its functions to supervise territories in the United Nations Trusteeship system. However, since 1994, the Trusteeship Council had been inactive. This does not heed to its history, where the Council had helped 11 trust territories in gaining independence. Interestingly, a handful of thee territories that had been assisted by the Council had in recent years encountered problems especially in its own governance systems. Those States had lost its capacity to govern itself, not able to withstand internal and external pressures of the modern world. Aside from former trust territorieas, there had been many instances of other States experiencing instability, that could be forwarded as to be included in the job description of the Trusteeship Council. A revival seems to befit the Council, taking into account recent development. Nonetheless, a litany legal and political hurdles must be passed before the Council could rise once again.